Mangrove Vegetation : Composition & Structure in Bengawan Solo Estuary, Indonesia - Ali, Mukti; Sulistiono, Sulistiono (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018DO - 10.14456/nujst.2018.27, 2018)
Recent damage to the mangrove ecosystem has threatened the existence of this ecosystem. The mangrove ecosystem of the Ujungpangkah area in the Bengawan Solo estuary is one of the few (pristine remaining) mangrove ecosystems in East Java Province of Indonesia. This study aims to investigate the type and structure of mangrove ecosystems in the Ujungpangkah coastal, region Gresik, East Java Province. The ecosystem structure was investigated using mangrove vegetation analysis and spatial analysis using Normalized Difference Vegetation Index system analysis. Based on spatial analysis, the mangrove area in the Ujungpangkah was 1.445 hectares distributed among 4 (four) villages, consisting of high density (650 hectares), medium density (453 hectares), and low density (342 hectares). This area comprised 7 (seven) mangrove species i . e . Avicenia marina, Rhizopora mucronata, Rhizopora apiculata, Bruguiera cylindrica, Excoecaria agallocha, Sonneratia alba and Bruguiera gymnorrhiza . The Avicenia marina and Rhizopora mucronata were two mangrove species with the highest important value index at each growth level. The highest value index (71.73%) was attributed to Avicenia marina for the tree level, while Rhizopora mucronata was dominant at the sapling level (82.55%). Keywords : Mangroves, Density, Ujungpangkah